Volcanogenic Fluvial-Lacustrine Environments in Iceland and Their Utility for Identifying Past Habitability on Mars - Claire Cousins (Life, 2015)
The search for once-habitable locations on Mars is increasingly focused on environments dominated by fluvial and lacustrine processes, such as those investigated by the Mars Science Laboratory Curiosity rover. The availability of liquid water coupled with the potential longevity of such systems renders these localities prime targets for the future exploration of Martian biosignatures. Fluvial-lacustrine environments associated with basaltic volcanism are highly relevant to Mars, but their terrestrial counterparts have been largely overlooked as a field analogue. Such environments are common in Iceland, where basaltic volcanism interacts with glacial ice and surface snow to produce large volumes of meltwater within an otherwise cold and dry environment. This meltwater can be stored to create subglacial, englacial, and proglacial lakes, or be released as catastrophic floods and proglacial fluvial systems. Sedimentary deposits produced by the resulting fluvial-lacustrine activity are extensive, with lithologies dominated by basaltic minerals, low-temperature alteration assemblages (e.g., smectite clays, calcite), and amorphous, poorly crystalline phases (basaltic glass, palagonite, nanophase iron oxides). This paper reviews examples of these environments, including their sedimentary deposits and microbiology, within the context of utilising these localities for future Mars analogue studies and instrument testing.